2020
DOI: 10.1155/2020/9254516
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Municipal Solid Waste Incinerator (MSWI) Bottom Ash as Alternatives of Subgrade Materials

Abstract: The rapid development of industrialization, urbanization, and population of the society augments the rising amount of municipal solid waste (MSW). With the advantage of considerably reducing mass and volume of solid wastes and generating energy, the incineration is a widely used treatment method for MSW. During the incineration process, the organic substances contained in the wastes are combusted, and the massive residues are remained. Of the incineration residues, bottom ash takes up to 80–90%, and the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…Because the heavy metal in fly ash is easy to leach, it must be pretreated before it is used as subgrade material. After solidification of fly ash cement, its strength can meet the requirements of subgrade, and the amount of heavy metal leaching is less [191]. In addition, fly ash can be directly used as subgrade material to waterproof subgrade.…”
Section: Application In Subgrade Materialmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the heavy metal in fly ash is easy to leach, it must be pretreated before it is used as subgrade material. After solidification of fly ash cement, its strength can meet the requirements of subgrade, and the amount of heavy metal leaching is less [191]. In addition, fly ash can be directly used as subgrade material to waterproof subgrade.…”
Section: Application In Subgrade Materialmentioning
confidence: 99%
“…e shear strength, elastic modulus, and bearing ratio of bottom ash are close to those of sand. When the bottom ash is mixed with sand or soil, the strength of the mixture can also be improved [182,191,194]. Bottom ash has been widely used as a subgrade filler, and the strength, stability, and durability are good [186].…”
Section: Application In Subgrade Materialmentioning
confidence: 99%
“…MSWI BA has been used in the field. Huang et al (2020) applied MSWI BA as an alternative to subgrade materials for HMA pavements, and the results indicated that the tensile strain at the bottom of the HMA layer was diminished, along with the compressive strain on top of the subgrade layer [152]. MSWI BA was used as an unbound granular subbase in France; the road pavement has been soundly in use for 20 years, and it exhibited a CBR value of >120%, according to FWD measurements [107].…”
Section: Geomaterials Applicationsmentioning
confidence: 99%
“…However, there are few studies on the constitutive relations of MSWIBA. When a stress-strain relationship model is selected to analyze a particular soil, there will be a lack of consideration of the changes in such a model under certain specific conditions, which will result in substantial errors (Lai et al 2007;Du et al 2020;Huang et al 2020). Suitable stress-strain relationship models should be selected depending on the soil properties (Chang et al 2015;Guo et al 2016); therefore, special attention should be paid to the constitutive relations of MSWIBA.…”
Section: Introductionmentioning
confidence: 99%